In Vitro Cytocompatibility and Anti‐biofilm Properties of Electrodeposited Ternary‐Ion‐Doped Hydroxyapatite Coatings on Ti for Orthopaedic Applications. Issue 4 (24th January 2023) - Bian, Anqi; Jia, Fenghuan; Wu, Zongze; Li, Meiyu; Yang, Hao; Huang, Xiao; Xie, Lei; Qiao, Haixia; Lin, He; Huang, Yong
Abstract: Currently, there is a growing market for implant coatings that efficiently ward off bacterial infections while aiding in clinical osseointegration. Due to its potential to have a number of functions (including osteogenic activity and antibacterial activity) for bone implantation, the hydroxyapatite (HA) coating doped with multiple ions has drawn a lot of attention. In this study, innovative nanohydroxyapatite coatings containing simultaneous Sr 2+, Mn 2+, and Ag + substitutions (MnSrAgHA) were devised and effectively electrodedeposited on pure titanium. That is, the antibacterial ability of MnSrAgHA was enhanced by Ag +, Sr 2+ and Mn 2+ not only can balance the potential cytotoxicity of Ag +, but also can improve the bone repair rate of composite materials. Some experimental (FE‐SEM, XPS and EDS, etc.) results about the characterization show that Sr 2+, Mn 2+ and Ag + can uniformly combine into the HA lattice to form the SrMnAgHA coating. The MnSrAgHA coating surface was rather dense, with numerous needle‐like or flower cluster crystals, and the coating thickness is approximately 10 μm. Moreover, compared with other coatings (HA, AgHA and SrAgHA), the MnSrAgHA coating had a smaller roughness and higher contact angle. However, the contact angle of MnSrAgHA was still within the hydrophilic range. Staphylococcus aureus growth was inhibited by the MnSrAgHA coating, and the antibacterial rate was almost 100 %. The MnSrAgHA coating dramatically enhanced cell proliferation, adhesion, and differentiation abilities, according to in‐vitro cell culture studies. As expected, osteoblasts are not significantly cytotoxic by the MnSrAgHA coating. Due to its adaptability, the multi‐element co‐doped HA coating (MnSrAgHA) offers enormous clinical application potential in anti‐infective repair. Abstract : The fabrication process of the MnSrAgHA composite coating on Ti is shown in Graphical Abstract (for review). A novel nano‐HA coating simultaneously substituted by Mn 2+, Sr 2+ and Ag + was successfully synthesized on titanium substrates by electrochemical deposition technique.The following series of experiments were verified: 1) the surface microstructure, phase composition, roughness, hydrophilicity of the coated implants; 2) the release behavior of Sr 2+, Ag + and Mn 2+ from the MnSrAgHA coating; 3) the in vitro cellular responses of the composite coatings; 4) Effect of Ag + on antibacterial properties of composite coatings.